Lipid Content and Composition during the Oocyte Development of Two Gorgonian Coral Species in Relation to Low Temperature Preservation - Lin, Chiahsin (Public Library of Science, 2012)
Our previous studies have suggested that chilling sensitivity of coral oocytes may relate to their relatively high lipid intracellular content and lipid composition. The distribution of lipids during the oocyte development was determined here for the first time in two gorgonian species (Junceella juncea and Junceella fragilis). The main lipid classes in the two gorgonian oocytes were total lipid, wax ester, triacylglycerol, total fatty acid, phosphatidylethanolamine and phosphatidylcholine. The results indicated that early stage oocytes of J. juncea and J. fragilis were found to have increased lipid content than late stage oocytes. The content of wax ester was significantly higher in the early stage oocytes of two gorgonian corals (51.0±2.5 and 41.7±2.9 µg/mm(3)/oocyte) than those of late stage oocytes (24.0±1.4 and 30.4±1.2 µg/mm(3)/oocyte, respectively). A substantial amount of phosphatidylethanolamine and total fatty acid was detected at each stage of oocyte development in two gorgonian ranges from 107 to 42 µg/mm(3)/oocyte and 106 to 48 µg/mm(3)/oocyte, whilst low levels of phosphatidylcholine were found in two gorgonian oocytes. The levels of total lipid in the late stage oocytes of J. juncea were significantly higher than those of J. fragilis. The observed differences may partially be related to different habitat preferences as higher lipid levels in J. juncea, a deeper-water coral species exposed to lower temperature seawater, might relate to adjustments of cell membranes in order to increase membrane fluidity.